Political Thought In Islam: An Analysis of The Development And Evolution of Islamic Political Philosophy - Salman Faris TC (MAQOLAT: Journal of Islamic Studies, 2024)
The explores the development and evolution of Islamic politics, tracing its historical trajectory from the early stages of Islam to its contemporary manifestations. By analyzing key political events, influential thinkers, and ideological movements, this study sheds light on the multifaceted nature of Islamic politics and its transformations over time. Through a comprehensive examination of primary and secondary sources, the research highlights the diverse political ideologies, organisations, and discourses within the Islamic tradition. Furthermore, it investigates the early Islamic period, the caliphate era, the influence of classical Islamic scholars, and contemporary debates on political philosophy in Islam. By examining various perspectives, this research aims to provide a comprehensive understanding of the rich and diverse political thought within the Islamic tradition.